2022
DOI: 10.1101/2022.03.28.486130
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Activation of the CA2-vCA1 pathway reverses social discrimination dysfunction inShank3Bknockout mice

Abstract: Social memory dysfunction is a feature of several neuropsychiatric and neurodevelopmental disorders. Mutation or deletion of the SHANK3 gene, which codes for a synaptic scaffolding protein, has been linked to autism spectrum disorder (ASD) and Phelan-McDermid syndrome, conditions associated with impairments in social memory. Shank3B knockout (KO) mice exhibit several behavioral abnormalities that may be analogous to symptoms of ASD, including social discrimination deficits. The CA2 region of the hippocampus in… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 99 publications
0
0
0
Order By: Relevance
“…Some autistic individuals have difficulty recognizing and recalling faces of strangers (Williams et al, 2005;Stantić et al, 2022). Similarly, the Shank3B model of ASD shows deficits in discriminating between a novel and a familiar mouse (Cope et al, 2023). In our social touch assay, we observed that Fmr1 KO mice (n=8-10) exhibit similar levels of aversion to forced social touch with a familiar mouse and a stranger mouse (same-sex) (Fig.…”
Section: Fmr1 Ko Mice Show Less Aversion To Social Touch With a Mouse...mentioning
confidence: 63%
See 1 more Smart Citation
“…Some autistic individuals have difficulty recognizing and recalling faces of strangers (Williams et al, 2005;Stantić et al, 2022). Similarly, the Shank3B model of ASD shows deficits in discriminating between a novel and a familiar mouse (Cope et al, 2023). In our social touch assay, we observed that Fmr1 KO mice (n=8-10) exhibit similar levels of aversion to forced social touch with a familiar mouse and a stranger mouse (same-sex) (Fig.…”
Section: Fmr1 Ko Mice Show Less Aversion To Social Touch With a Mouse...mentioning
confidence: 63%
“…Finally, we observed ASD mice display similar levels of avoidance and AFEs in response to forced social touch from a familiar mouse relative to a stranger mouse. This finding was not unusual given that both ASD individuals and mouse models display deficits in social memory (Williams et al, 2005;Stantić et al, 2022;Cope et al, 2023).…”
Section: Discussionmentioning
confidence: 79%
“…The novelty T-maze focuses on both spatial learning and memory, and with its short, 1-minute inter-trial interval, this procedure is examining spatial working memory (Sharma et al, 2010; d’Isa et al, 2021). The 3-chamber social interaction test is assessing baseline sociability and also social recognition memory (Meira et al, 2018; Tzakis and Holahan, 2019; Wang and Zhan, 2022; Cope et al, 2023; Wei et al, 2024). Finally, the Barnes maze tests both spatial learning and working memory in intra-day trials, while simultaneously testing long-term contextual and spatial memory in inter-day trials and the probe test (Bach et al, 1995; Sharma et al, 2010; Rosenfeld and Ferguson, 2014; Pitts, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Loss of Prosapip1 in CA1 is likely leading to decreased performance in the novel object recognition, novelty T-maze, and Barnes maze tests. The lack of social recognition displayed by Prosapip1(flx/flx);Syn1-Cre(+) mice and AAV-Cre-infected mice is likely attributed to the loss of Prosapip1 in the CA2 subregion of the dHP, which is the primary subregion controlling social recognition memory (Meira et al, 2018; Tzakis and Holahan, 2019; Wang and Zhan, 2022; Cope et al, 2023; Wei et al, 2024). Specifically, silencing the CA2 subregion of the dHP impairs social memory formation and consolidation (Meira et al, 2018).…”
Section: Discussionmentioning
confidence: 99%